NUCLEOSYNTHETIC ZIRCONIUM ISOTOPE ANOMALIES IN ACID LEACHATES OF CARBONACEOUS CHONDRITES - Schönbächler M.; Rehkämper M.; Fehr M.A.; Halliday A.N.; Hattendorf B.; Günther D. (My University, 2005)
Stepwise dissolutions of the carbonaceous chondrites Orgueil (CI), Murchison (CM) and Allende (CV) reveal large nucleosynthetic anomalies for Zr isotopes that contrast with the uniform compositions found in bulk meteorites. Two complementary nucleosynthetic components are observed: one enriched and one depleted in s-process nuclides. The latter component, characterized by excess 96Zr, is most distinctive in the acetic acid leachate (up to ε96Zr ≈ 50). The excess decreases with increasing acid strength and the final leaching steps of the experiment are depleted in 96Zr and thus enriched in s-process nuclides. Presolar silicon carbide grains are likely host phases for part of the anomalous Zr released during these later stages. However, by mass balance they cannot account for the 96Zr excesses observed in the early leaching steps and this therefore hints at the presence of at least one additional carrier phase with significant amounts of anomalous Zr. The data provide evidence that average solar system material consists of a homogenized mixture of different nucleosynthetic components, which can be partly resolved by leaching experiments of carbonaceous chondrites.